INCREASING STUDENTS’ VOCABULARY MASTERY THROUGH “MOBILE LEGENDS” GAME ONLINE APPLICATION AT SMA NEGERI 4 MAKASSAR - Khairunnisa Rachman; Restu Januarty; Muliati (Lembaga Jurnal FKIP Universitas Bosowa, 2022)
The objective of the research was to know the students' vocabulary mastery through Mobile Legends game online application and to find out the affect of Mobile Legends Game online application on students' vocabulary mastery. This research uses the pre-experimental research method. The population of this research were the students of the second-grade of SMA Negeri 4 Makassar in 2022/2023 academic year, with sample were 30 students. The researcher collected the data by giving pre-test and post-test. The data of this research was analyzed by SPSS 24 Version. Based on the results of data analysis, the researcher concluded that the use of Mobile Legends Game online application can increase students' vocabulary mastery, it's proved by the mean score of the students in pretest and post-test. The result of the research shows that Mobile Legends Game online application was significantly increased students' vocabulary mastery. The mean score in pre-test was 52.83, while in post-test was 81.83. It indicated that the one hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. It means that Mobile Legends Game online application could increase the students' vocabulary mastery in learning English at SMA Negeri 4 Makassar. The objective of the research was to know the students' vocabulary mastery through Mobile Legends game online application and to find out the affect of Mobile Legends Game online application on students' vocabulary mastery. This research uses the pre-experimental research method. The population of this research were the students of the second-grade of SMA Negeri 4 Makassar in 2022/2023 academic year, with sample were 30 students. The researcher collected the data by giving pre-test and post-test. The data of this research was analyzed by SPSS 24 Version. Based on the results of data analysis, the researcher concluded that the use of Mobile Legends Game online application can increase students' vocabulary mastery, it's proved by the mean score of the students in pretest and post-test. The result of the research shows that Mobile Legends Game online application was significantly increased students' vocabulary mastery. The mean score in pre-test was 52.83, while in post-test was 81.83. It indicated that the one hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. It means that Mobile Legends Game online application could increase the students' vocabulary mastery in learning English at SMA Negeri 4 Makassar.